IEEE Congress on Evolutionary Computation 2010
DOI: 10.1109/cec.2010.5586233
|View full text |Cite
|
Sign up to set email alerts
|

Concurrently evolving sensor morphology and control for a hexapod robot

Abstract: Abstract-Evolving a robot's sensor morphology along with its control program has the potential to significantly improve its effectiveness in completing the assigned task, plus accommodates the possibility of allowing it to adapt to significant changes in the environment. In previous work, we presented a learning system where the angle, range, and type of sensors on a hexapod robot, along with the control program, were evolved. The evolution was done in simulation and the tests, which were also done in simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Despite these highly stimulating works, the role of the size, shape and placement of the sensors, commonly known as sensor morphology, does not seem to have been thoroughly investigated. While the importance of sensor morphology in determining the sensing characteristics and performance has gained a lot of attention in biology [ 24 , 25 ], embodied intelligence [ 26 ], and most recently in robotics [ 27 , 28 ], its role in soft body sensing still remains as a challenge. The sensorization solutions so far have had the potential for enabling customizable sensor morphology, but required complex molding and suggested casting processes for integration [ 13 , 29 ] or realized commonly used sensor morphologies [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these highly stimulating works, the role of the size, shape and placement of the sensors, commonly known as sensor morphology, does not seem to have been thoroughly investigated. While the importance of sensor morphology in determining the sensing characteristics and performance has gained a lot of attention in biology [ 24 , 25 ], embodied intelligence [ 26 ], and most recently in robotics [ 27 , 28 ], its role in soft body sensing still remains as a challenge. The sensorization solutions so far have had the potential for enabling customizable sensor morphology, but required complex molding and suggested casting processes for integration [ 13 , 29 ] or realized commonly used sensor morphologies [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…optimizing the thickness of convex lens to minimize ray scattering [91]. However, as also shown by examples [33,34,[80][81][82][83][84][85], there are more aspects to consider in the problem of optimizing sensor morphology from bioinspired robotics perspective, such as co-optimization between motor control and morphology, gaps between simulation and real-world implementation, or how factors such as material properties or multiagent setting affect the design (see [92] for a review of the current progress of evolutionary algorithm applications rsfs.royalsocietypublishing.org Interface Focus 6: 20160016 in robotics), which also shows the importance of an integrative view.…”
Section: Adaptation Over Multiple Timescalesmentioning
confidence: 96%
“…the type of the sensed physical phenomenon, such as visual (light) [20 -27,32,33,35-46], somatosensory (touch and perception) [47,48,49,[50][51][52][53][54][55][56][58][59][60][61][62][63][64][65][66][67][68], auditory (hearing) [71,72] and even electric [73][74][75][76][77] or magnetic field [78,79]. Some researchers also investigated sensor morphology of multimodal systems, where a combination of multiple sensors is used, each sensing a different physical phenomenon [80][81][82][83][84].…”
Section: The Research Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…In robotics research, there are several attempts to exploit this interdependence in order to accomplish different kinds of sensing tasks with suitable performance. For example, it has been shown that concurrently evolving the sensors placement and the motion control significantly improve the effectiveness of hexapod robot navigation [ 13 ]. In multi-robot setting, the interdependence between sensor morphology and the motion of each robot has also been studied in a context of formation control [ 14 ].…”
Section: Introductionmentioning
confidence: 99%